Two-Stage Combined Ortho-Plastic Management of Type IIIB Open Diaphyseal Tibial Fractures Requiring Flap Coverage: Is the Timing of Debridement and Coverage Associated With Outcomes?. Issue 12 (December 2019) - Al-Hourani, Khalid; Fowler, Tim; Whitehouse, Michael R.; Khan, Umraz; Kelly, Michael
Abstract : Objective: To delineate whether timing to initial debridement and definitive treatment had an effect on patient outcomes in those undergoing 2-stage ortho-plastic management of Gustilo–Anderson type IIIB open tibial diaphyseal fractures. Design: Retrospective comparative cohort study over a 2-year period. Setting: Level 1 trauma center. Patients/Participants: A total of 148 patients were identified. After exclusion of ankle fractures, nondiaphyseal fractures and those who did not undergo 2-stage ortho-plastic management, 45 patients were eligible for final analysis. Intervention: Time to initial debridement and definitive management. Main Outcome Measurement: Deep infection. Secondary outcomes being nonunion and flap failure. Multiple linear regression was used for outcomes. We assumed a priori that P values of less than 0.05 were significant. Results: Mean age was 54 years (SD 23.0), with 28 men and 17 women. Over a mean 2-year follow-up, there were 4 (4/45) deep infections, 2 infection-associated flap failures, and 1 vascular flap failure. All patients progressed to union. The mean time to initial debridement for the whole cohort was 19 hours (SD 12.3), and the mean time to definitive reconstruction was 65 hours (SD 51.7). Longer time to both initial debridement and definitive reconstruction was not found to be significantly associated with deep infection, infected flap failure, or nonunion. Conclusions: Using a 2-stage ortho-plastic operative algorithm, timing to initial debridement and definitive fixation with soft-tissue coverage was not associated with negative outcomes. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.